Anthology of children's literature - Johnson, Edna (Houghton Mifflin, 1959)
An anthology of nursery rhymes, poetry, epics, mythology and folklore, fiction, and non-fiction for children. Appendices include notes on storytelling, the history of children's literature, illustrators of children's books, children's book awards, graded reading lists, and biographical sketches.